FRI0151 COMORBIDITY IN INCIDENT SYSTEMIC LUPUS ERYTHEMATOSUS: ANALYSIS OF A CLAIMS DATA COHORT. (13th June 2020) - Albrecht, K.; Redeker, I.; Aringer, M.; Marschall, U.; Zink, A.; Callhoff, J.
Abstract : Background: Systemic lupus erythematosus (SLE) targets many tissues including heart, kidney, bone and brain, causing a variety of comorbidities. Epidemiological studies assessing comorbidity in SLE facilitate earlier detection to limit its progression. Objectives: To analyze comorbidities in individuals with an incident diagnosis of systemic lupus erythematosus (SLE) in claims data in comparison to matched controls. Methods: Individuals with ≥2 outpatient or 1 inpatient SLE diagnosis (M32.1, M32.8, M32.9, ICD10) in 2016-2018 and no diagnosis in 2015 or 2014 were identified in a German statutory health insurance fund covering 7.2 million people > 18 years old. Comorbidities defined by the Elixhauser index, medical prescriptions, hospitalization and sick leave were analyzed in the year prior to diagnosis and during a two year follow-up in comparison to age and sex-matched controls without related autoimmune diseases (1:10). To account for detection bias, a second age and sex-matched control group with incident diabetes mellitus (E10-14) was drawn (1:5). To consider diagnostic uncertainty, two sensitivity analyses were performed, namely (i) excluding cases with ICD diagnosis of Sjögren's syndrome, mixed connective tissue disease, systemic sclerosis and tubulointerstitial nephritis and (ii) excluding cases without any prescription of antimalarials. Results: A total of 559 persons were included (87% female, mean age 55 years). The mean Elixhauser score increased from 1.1 in 2015 to 4.2 in the index year and to 4.5 in the 2nd year after diagnosis. Hypertension (47%), depression (31%), hyperlipidemia (25%), osteoarthritis (25%) and osteoporosis (21%) were among the most frequent comorbidities in the index year. Drug prescriptions (mean 9.7, Δ+6.3), among these glucocorticoids (56%), HCQ (50%) and azathioprine (13%), and hospitalization (40%, Δ+26%) increased in the 1st year after the SLE diagnosis. The increase in comorbidity diagnoses was low in controls without related autoimmune disease, while controls with incident diabetes showed a more pronounced increase in cardiovascular risk factors and and a lesser increase in osteoporosis and cerebrovascular disease (figure 1 ). Comparable results were found in the sensitivity analyses, where patients with HCQ were younger and had less general comorbidity. Conclusion: Cardiovascular, bone and neurologic comorbidities are frequently detected already at the time of diagnosing SLE. High numbers of medical prescriptions and hospitalization following SLE diagnosis reflect the comprehensive disease burden. Differences to controls without autoimmune disease are overestimated by detection bias. References: Funding The study was supported by the Wolfgang Schulze Foundation of the German Rheuma-Liga Disclosure of Interests: Katinka Albrecht: None declared, Imke Redeker: None declared, Martin Aringer Consultant of: Boehringer Ingelheim, Roche, Speakers bureau: Boehringer Ingelheim, Roche, Ursula Marschall: None declared, Angela Zink Speakers bureau: AbbVie, Amgen, BMS, Gilead, Hexal, Janssen, Lilly, MSD, Pfizer, Roche, Sanofi Aventis, UCB, Johanna Callhoff: None declared